Surgical management of an appendiceal neurofibroma in a neurofibromatosis-1 patient: A case report - Averi Wilson; John Slopis; Richard Andrassy; Sadhna Dhingra; Mary Austin (Elsevier, 2015)
Neurofibromatosis-1 (NF1) is an autosomal dominant disease with an incidence of 1 in every 2500 to 3000 births [1]. Although neurofibromas that result from the NF1 gene mutation are typically benign, they may cause complications by compressing neighboring structures or undergoing malignant transformation. The various manifestations and symptoms of NF1 may cause a number of complications throughout childhood and into adulthood, and patients often require surgical management of these complications. A young adult with a previous NF1 diagnosis presented with symptoms concerning for appendicitis. Subsequent imaging and biopsy revealed a rare appendiceal neurofibroma. The patient underwent an ileocecectomy and pathology confirmed the diagnosis of appendiceal neurofibroma. The variety of symptoms and complications associated with NF1, such as vascular abnormalities and airway obstruction, create unique surgical risks for these patients. These risks should be understood and accounted for by surgeons who may encounter NF1 patients.